Practices and challenges of safety management in outsourced facilities management - Pilbeam, Colin (Elsevier, 2024)
Introduction: Outsourcing is a commonly occurring organizational activity, but one associated with negative occupational safety outcomes. Improving the management of safety in workplaces where contractors are employed is vital, but under-researched in the service sectors. The aims of this paper were to investigate both the practices and challenges of safety management in outsourced facility management (FM), an important global service sector. Method: Twenty-three semi-structured interviews were conducted with clients and contractors in three different FM outsourcing arrangements between large corporations in the UK. Data were thematically coded against frameworks derived from existing literature to identify deployed safety management practices and reveal challenges associated with safety management in these outsourced relationships. Results: Safety management practices in outsourced FM conformed to known practices clustering into four previously identified categories (planning, selecting, on-site working, and checking). A fifth category (reviewing) was not observed. Operating across national boundaries, applying national contracts locally, working with mandated KPIs, and contract specifications all created new challenges for safety management not previously reported. Other known challenges associated with economic pressure and disorganization were observed. Conclusion: Safety management practices observed in safety critical industries also apply in FM. However, the challenges of safety management in these three cases included regulatory failures that have not been routinely identified in other empirical studies of safety in outsourcing arrangements. Practical application: Adopting widely accepted safety management practices support safer working in outsourced FM and encourage cross-sector learning. New challenges for safety management noted here encourage consideration of unintended consequences of contract terms and conditions, require corporate agreement on how to ensure safety compliance when working transnationally, and a review of decision-making and processes and procedures to enable effective and safe working locally.
Keywords: Contractor; Outsourcing; Health and safety; Facility management; Safety management system